ANALISIS PROVENANCE, DIAGENESIS DAN LINGKUNGAN PENGENDAPAN SERTA PENGARUH TERHADAP KUALITAS RESERVOIR BATUPASIR FORMASI TALANG AKAR, SUMUR FA-21, CEKUNGAN JAWA BARAT UTARA - Fahmi Abdillah; Hadi Nugroho; Fahrudin Fahrudin; Agus Priyantoro (Geological Engineering E-Journal, 2014)
The necessary of technology at this time resulted the necessary of energy resources will increasing, and it also result the scarcity of energy resources. One of the energy resources that is still used as a major energy resource is oil and gas. To overcome these problems, exploration activities at this time needs to be further improved. In the field of exploration, one of the most important things to know is reservoir. Reservoir quality is important for us to know so that we can determine whether an area has hydrocarbon potential to be developed or not. The main parameters of reservoir quality are porosity and permeability.In this study discussed the analysis of provenance, diagenetic and depositional environment of the sandstone reservoir of Talang Akar Formation, North West Java Basin and from the results of the analysis will be associated with the effect on reservoir quality. To determine the reservoir quality based on these parameters, can be done by several methods such as petrographic, cores, SEM and XRD analysis. From the analysis that has been done can be seen that the provenance of Talang Akar sandstone is Granite. So it can be seen that the Talang Akar sandstone which the provenance is Granite has good reservoir quality, with porosity values ranging from 19.04% to 24.28% and permeability ranging between 30-674 mD or belonging to the class good - very good (Koesoemadinata, 1980). Then the diagenetic process that occurs is compaction, cementation, replacement and dissolution. The process of compaction, cementation and replacement leads to reduced rock porosity values ranging from 2.25 to 11.5%, while the dissolution process resulting in increased rock porosity is about 1.5 - 2%. The depositional environment of the Talang Akar Sandstone is Upper Delta front. Rock facies in the upper delta front has good reservoir quality, with porosity values range from 19.04% to 24.28% and permeability range between 30-674 mD or belonging to the class is good - very good (Koesoemadinata, 1980).